Do dental bleaching sessions prior to orthodontic treatment change the bond strength of esthetic brackets? - Samara Gasperoni PERCIANO; Diego Patrik Alves CARNEIRO; Patricia Rafaela dos SANTOS; Américo Bortolazzo CORRER; Silvia Amélia Scudeler VEDOVELLO; Heloísa Cristina VALDRIGHI (Dental Press Editora, 2021)
ABSTRACT Objective: The aim of this experimental in vitro study was to evaluate whether dental bleaching performed before orthodontic treatment change the shear bond strength (SBS) of monocrystalline and polycrystalline esthetic brackets. Methods: Sixty (60) bovine incisors teeth were used and randomly divided into the following six groups (n=10): SCP (without bleaching/polycrystalline brackets); SCM (without bleaching/monocrystalline brackets); 1CP (one bleaching session/polycrystalline brackets); 1CM (one bleaching session/monocrystalline brackets); 3CP (three bleaching sessions/polycrystalline brackets); and 3CM (three bleaching sessions/monocrystalline brackets). The brackets were bonded seven days after the bleaching sessions. The samples were submitted to the SBS test in a universal testing machine (Instron model 4411) at 1 mm/min crosshead speed. The two-way analysis of variance (ANOVA) and the Tukey tests were performed at a 5% level of significance. After the mechanical test, samples were evaluated to determine the adhesive remnant index (ARI). Results: The SBS values were significantly higher for the monocrystalline brackets, when compared with the polycrystalline type (p< 0.0001), and significantly higher with three bleaching sessions than without bleaching (p< 0.0436). The ARI showed predominance of failures between the bracket and resin for all the groups (score 3). Conclusion: Three dental bleaching sessions increased the SBS values. Monocrystalline brackets showed higher SBS values than the polycrystalline type.